Extending the memorable tourism experience construct : an investigation of memories of local food experiences - Sthapit, Erose; Coudounaris, Dafnis; Björk, Peter (Scandinavian Journal of Hospitality and Tourism, 2022)
This study proposes and tests a new model of memorable local food experiences by examining the effect of the servicescape, novelty seeking, experience co-creation, choice overload and experience intensification on memories of local food experiences. The study also examines how such experiences impact hedonic well-being. Using an online survey questionnaire, data were gathered from 321 international tourists who tasted local food while visiting Rovaniemi, Finland, in the past year. The present study’s main contributions include the extension of the memorable tourism experience construct and the inclusion of experience co-creation, the servicescape and experience intensification as crucial variables that affect tourists’ memorable local food experiences. This paper also extends the bottom-up spillover theory of subjective well-being by demonstrating that memories of local food experiences allow for the intrusion of the extraordinary into tourists’ residual culture, thereby benefitting them while at home by promoting their well-being. Peer reviewed